Preclinical development of a chimeric antigen receptor T cell therapy targeting FGFR4 in rhabdomyosarcoma - Tian, Meijie; Wei, Jun S.; Shivaprasad, Nityashree; Highfill, Steven L.; Gryder, Berkley E.; Milewski, David; Brown, G. Tom; Moses, Larry; Song, Hannah; Wu, Jerry T.; Azorsa, Peter; Kumar, Jeetendra; et al. (Cell reports. Medicine, 2023)
Pediatric patients with relapsed or refractory rhabdomyosarcoma (RMS) have dismal cure rates, and effective therapy is urgently needed. The oncogenic receptor tyrosine kinase fibroblast growth factor receptor 4 (FGFR4) is highly expressed in RMS and lowly expressed in healthy tissues. Here, we describe a second-generation FGFR4-targeting chimeric antigen receptor (CAR), based on an anti-human FGFR4-specific murine monoclonal antibody 3A11, as an adoptive T cell treatment for RMS. The 3A11 CAR T cells induced robust cytokine production and cytotoxicity against RMS cell lines in vitro. In contrast, a panel of healthy human primary cells failed to activate 3A11 CAR T cells, confirming the selectivity of 3A11 CAR T cells against tumors with high FGFR4 expression. Finally, we demonstrate that 3A11 CAR T cells are persistent in vivo and can effectively eliminate RMS tumors in two metastatic and two orthotopic models. Therefore, our study credentials CAR T cell therapy targeting FGFR4 to treat patients with RMS. [Display omitted] •FGFR4 is highly expressed in rhabdomyosarcoma and lowly expressed in healthy human tissue•FGFR4 is a downstream target of the PAX3-FOXO1 fusion oncogene•FGFR4 CAR T cells demonstrate no cytokine release against primary human cells•FGFR4 CAR T cells eliminate metastatic and intramuscular solid RMS tumors in vivo Tian et al. develop a potent clinical-grade CAR targeting FGFR4 that is highly expressed in rhabdomyosarcoma. FGFR4 CAR T cells show specific cytotoxicity against RMS cell lines and are non-reactive to healthy human primary cells. These CAR T cells eliminate tumors in metastatic and orthotopic mouse models of RMS.